New Horizons for Germany's Africa Policy - Robert Kappel (German Institute of Global and Area Studies (GIGA), 2017)
This paper deals with Germany's new Africa policy. The Federal Ministry for Economic Cooperation and Development (BMZ) presented a new Africa concept in January 2017. The BMZ wants to counter the further marginalisation of Africa with inclusive and sustainable growth. Chancellor Angela Merkel will explain her new policy for Africa at the G20 summit in Hamburg in July 2017, in an attempt to gain the approval of the other G20 members for focused cooperation with Africa. The paper argues that it remains solely the duty of African states to take their development into their own hands. Cooperation can support this process, but it cannot assume what is each state's individual responsibility. The Marshall Plan with Africa aims to develop a joint agenda with the countries of Africa. Yet because the African countries did not participate in developing the concept, the plan derived so far is more of a plan for Africa, identifying which measures the BMZ would like to implement in order to contribute to sustainable and inclusive economic growth in Africa. Africa is becoming increasingly differentiated, and developing a joint strategy with individual countries or groups of countries that reflects the varying speeds at which changes are occurring would be a decisive step. The plan does not cover sufficient ground on this issue. In order to develop a coherent Africa concept for the German federal government, the participation of the most important ministries needs to be improved, and the chancellor needs to be in charge of the overall management. The paper concludes that Germany's Africa policy needs to be redesigned. The Marshall Plan has generated a shift, but it does not provide sufficient guidance to new horizons and away from the well-beaten track of traditional development cooperation. The departure to a new age that is defined by increased cooperation with democratic African countries which are capable of reform, and by a courageous and consistent stance in relation to non-democratic countries, has not yet taken place.
Keywords: 300; Africa; German Africa policy; Compact with Africa; Marshall Plan with Africa; Cooperation